2017
DOI: 10.1002/2017tc004703
|View full text |Cite
|
Sign up to set email alerts
|

Phanerozoic Morphotectonic Evolution of the Zimbabwe Craton: Unexpected Outcomes From a Multiple Low‐Temperature Thermochronology Study

Abstract: The fragmentary Phanerozoic geological record of the anomalously elevated Zimbabwe Craton makes reconstructing its history difficult using conventional field methods. Here we constrain the cryptic Phanerozoic evolution of the Zimbabwe Craton using a spatially extensive apatite (U‐Th‐Sm)/He (AHe), apatite fission track (AFT), and zircon (U‐Th)/He (ZHe) data set. Joint thermal history modeling reveals that the region experienced two cooling episodes inferred to be the denudational response to surface uplift. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 149 publications
4
37
0
Order By: Relevance
“…In addition, the low‐temperature sensitivity and radiation damage influences on the apatite He system make it ideal for quantifying the timing, magnitude, and extent of low (<2 km) amplitude deposition and denudation episodes in cratonic regions, even when the deposited rocks have been completely eroded from the rock record. Apatite He date‐eU relationships inform long‐term thermal histories linked to these surface processes (e.g., Ault et al, , ; Ault, Flowers, & Bowring, ; Flowers, ; Flowers et al, ; Guenthner et al, ; Mackintosh et al, ). Figure presents apatite He, AFT, and zircon He data patterns from across the interior of continental North America.…”
Section: Low‐temperature Thermochronometry Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the low‐temperature sensitivity and radiation damage influences on the apatite He system make it ideal for quantifying the timing, magnitude, and extent of low (<2 km) amplitude deposition and denudation episodes in cratonic regions, even when the deposited rocks have been completely eroded from the rock record. Apatite He date‐eU relationships inform long‐term thermal histories linked to these surface processes (e.g., Ault et al, , ; Ault, Flowers, & Bowring, ; Flowers, ; Flowers et al, ; Guenthner et al, ; Mackintosh et al, ). Figure presents apatite He, AFT, and zircon He data patterns from across the interior of continental North America.…”
Section: Low‐temperature Thermochronometry Applicationsmentioning
confidence: 99%
“…Apatite, zircon, and titanite date-eU relationships (e.g., Figure 3) are a powerful tool for reconstructing protracted thermal histories characteristic of ancient bedrock (Ault et al, 2009(Ault et al, , 2013Ault et al, 2018;Baughman & Flowers, 2018;DeLucia et al, 2018;Flowers, 2009;Flowers et al, 2007;Guenthner et al, 2013Guenthner et al, , 2014Guenthner et al, , 2017Johnson et al, 2017;Mackintosh et al, 2017;Orme et al, 2016;Powell et al, 2016;Weisberg et al, 2018). Damage-diffusivity patterns can be predicted given a thermal history or inverted to derive a thermal history using HeFTy or QTQt.…”
Section: 1029/2018tc005312mentioning
confidence: 99%
“…Guenthner et al () suggested that the correlation is a product of intragrain differences in accumulated radiation damage in zircons. In certain cases, such variations result in varying He diffusion rates (or He retentivity) between aliquots, effectively lowering the temperature range of the PRZ for grains with significant radiation damage (e.g., Johnson et al, ; Mackintosh et al, ). The age‐eU relationship observed in shallower Lapur basement samples is interpreted as indicating age dispersion as the product of variations in He diffusivity related to different amounts of α radiation damage accumulation.…”
Section: Datamentioning
confidence: 99%
“…By employing AFT, apatite (U-Th-Sm)/He (AHe) and zircon (U-Th)/He (ZHe) thermochronometry, we reconstruct the thermal history of a sample through a range of potentially ~30-220 °C (equivalent to <1-8 km assuming a typical mobile belt geothermal gradient of 25 °C/km (Nyblade et al, 1990) and surface temperature of 20 °C). Indeed, the different temperature sensitivities of the AHe, AFT and ZHe systems-typically ranging from ~30-90 °C (Flowers et al, 2009), ~60-110 °C (Gleadow et al, 2002) and <50-220 °C (Guenthner et al, 2013;Johnson et al, 2017;Mackintosh et al, 2017), respectively-provide insight into different portions of the morphotectonic history.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…the He partial retention zone (PRZ) (Wolf et al, 1998), controlled by numerous grainspecific factors, including the amount of accumulated radiation damage (Guenthner et al, 2013;Shuster et al, 2006), grain size (Reiners et al, 2004;Reiners and Farley, 2001) and parent nuclide heterogeneity (Farley et al, 2011;Hourigan et al, 2005). In both systems, radiation damage is the main control on the temperature sensitivity range such that the He PRZs of individual grains can vary from ~30-90 ºC for the AHe system (Flowers et al, 2009;Gautheron et al, 2009) and <50-220 ºC (Anderson et al, 2017;Guenthner et al, 2013;Johnson et al, 2017;Mackintosh et al, 2017) for the ZHe system. Some other factors affect the measured parent-daughter ratio and in turn, the measured AHe and ZHe ages.…”
Section: Apatite and Zircon (U-th)/he Analysismentioning
confidence: 99%